2018
DOI: 10.1007/s10899-018-9782-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of At-Risk Gamblers’ Temporary Self-Exclusion from Internet Gambling Sites

Abstract: To prevent risks associated with online gambling, many jurisdictions propose self-exclusion strategies as a part of a responsible gambling policy. To protect online gamblers, French law provides for a 7-day temporary non-reducible and voluntary self-exclusion measure that applies only to select websites. The objective of our study was to evaluate the effectiveness of this self-exclusion measure for at-risk online gamblers. It was an experimental randomized controlled trial targeted at risk prevention. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 17 publications
2
35
0
Order By: Relevance
“…The efficacy of short self-exclusions among the most heavily involved gamblers was not supported by our data. This is in line with recent experimental data among problem gamblers suggesting no efficacy of very short self-exclusions on gambling outcomes [10]. Another qualitative study reported a preferred duration to ensure efficacy of 12 months from the perspective of problem gamblers who self-excluded [22].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The efficacy of short self-exclusions among the most heavily involved gamblers was not supported by our data. This is in line with recent experimental data among problem gamblers suggesting no efficacy of very short self-exclusions on gambling outcomes [10]. Another qualitative study reported a preferred duration to ensure efficacy of 12 months from the perspective of problem gamblers who self-excluded [22].…”
Section: Discussionsupporting
confidence: 87%
“…No study has reported efficacy data on spontaneous voluntary self-exclusion as compared to no intervention (i.e., no self-exclusion). One experimental study randomized volunteering problem gamblers (but not pathological gamblers, who were excluded) to either a very short 7-day period of self-exclusion or no self-exclusion [10]. The authors reported no significant between-group differences in terms of changes regarding money and time spent gambling at two months.…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary self-exclusion is a harm-minimization strategy for individuals who experience gambling problems. In the case of online gambling, it consists of voluntarily banishing oneself from gambling websites for a predefined period [ 57 ]. Voluntary self-exclusion is considered a valid proxy indicator to externally verify which individuals have gambling problems [ 20 ], and thus, reinforced our deduction that individuals in class 5 may have gambling problems.…”
Section: Discussionmentioning
confidence: 99%
“…gov/pmc/articles/PMC4448208/ (26). The MOD&JEU research program is composed of four randomized controlled studies assessing the effectiveness of various types of Internet gambling protection tools [self-limitation, pop-up messages, and selfexclusion (27)] and the impact of wagering inducements on gambling behaviors. The present work reports the results of the study dedicated to wagering inducements.…”
Section: Methodsmentioning
confidence: 99%